DOXIL when combined with Withaferin A (WFA) targets ALDH1 positive cancer stem cells in ovarian cancer - Kakar, Sham S. (J Cancer Stem Cell Res, 2016)
Ovarian cancer is a highly aggressive and deadly disease. Currently, the treatment for ovarian cancer entails cytoreductive surgery followed by chemotherapy, mainly cisplatin or carboplatin combined with paclitaxel. Although this regimen is initially effective in a high percentage of cases, unfortunately, after few months of initial treatment, tumor relapse occurs due to platinum-resistance. DOXIL (liposomal preparation of doxorubicin) is a choice of drug for recurrent ovarian cancer. However, its response rate is very low and is accompanied by myocardial toxicity. Resistance to chemotherapy and recurrence of cancer is primarily attributed to the presence of cancer stem cells (CSCs), a small population of cells present in cancer. Effect of DOXIL and withaferin A (WFA), both alone and in combination, was investigated on cell proliferation of ovarian cancer cell line A2780 and tumor growth in SCID mice bearing i.p. ovarian tumors. ALDH1 cells were isolated from A2780 using cell sorter, and effect of DOXIL and WFA both alone and in combination on tumorigenic function of ALDH1 was studied using spheroids formation assays in vitro. Western blots were performed to examine the expression of ALDH1 and Notch 1 genes. In our studies, we showed, for the first time, that DOXIL when combined with withaferin A (WFA) elicits synergistic effect on inhibition of cell proliferation of ovarian cancer cells and inhibits the expression of ALDH1 protein, a marker for ALDH1 positive cancer stem cells (CSCs), and Notch1, a signaling pathway gene required for self-renewal of CSCs. Inhibition of expression of both ALDH1 and Notch1 genes by WFA was found to be dose dependent, whereas DOXIL (200 nM) was found to be ineffective. SCID mice, bearing i.p. ovarian tumors, were treated with a small dose of DOXIL (2 mg/kg) in combination with a sub-optimal dose of WFA (2 mg/kg) which resulted in a highly significant (60% to 70%) reduction in tumor growth, and complete inhibition of metastasis compared to control. In contrast, WFA treatment showed a significant reduction in tumor growth but no change in metastasis compared to control. DOXIL showed non-significant reduction in tumor growth and no change in metastasis compared to control. Isolated ALDH1 positive CSCs treated with the combination of DOXIL and WFA resulted in a significant reduction in spheroids formation (tumorigenic function of CSCs) and expression of ALDH1 protein. WFA when used alone at a concentration of 1.5 μM was found to be highly effective in suppression of ALDH1 expression, whereas DOXIL at a concentration of 200 nM was found to be ineffective. DOXIL in combination with WFA elicits synergistic effects, targets cancer stem cells, and has potential to minimize induction of drug resistance and reoccurrence of cancer. Based on our studies, we conclude that the combination of DOXIL with WFA has the potential to be an effective therapy for ovarian cancer and may ameliorate DOXIL related side effects as well as recurrence of ovarian cancer leading to increase in patients’ survival rate.